2008
DOI: 10.1093/brain/awn145
|View full text |Cite
|
Sign up to set email alerts
|

Different structures involved during ictal and interictal epileptic activity in malformations of cortical development: an EEG-fMRI study

Abstract: Malformations of cortical development (MCDs) are commonly complicated by intractable focal epilepsy. Epileptogenesis in these disorders is not well understood and may depend on the type of MCD. The cellular mechanisms involved in interictal and ictal events are notably different, and could be influenced independently by the type of pathology. We evaluated the relationship between interictal and ictal zones in eight patients with different types of MCD in order to better understand the generation of these activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
137
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 71 publications
18
137
1
Order By: Relevance
“…Ictal events lacking significant clinical symptoms, particularly movements, are particularly wellsuited for recording in the MRI scanner, as motion may result in highly contaminated fMRI data . Compared to other studies in the literature (Di Bonaventura et al, 2006a;Kobayashi et al, 2006;Salek-Haddadi et al, 2002;Tyvaert et al, 2008), the 15 patients in the current study constitute a sizable number, but ictal events are still quite infrequently recorded during EEG-fMRI sessions. However, it should be noted that none of the patients had originally been recruited on the basis of their seizure frequency.…”
Section: Ictal Eventsmentioning
confidence: 75%
See 3 more Smart Citations
“…Ictal events lacking significant clinical symptoms, particularly movements, are particularly wellsuited for recording in the MRI scanner, as motion may result in highly contaminated fMRI data . Compared to other studies in the literature (Di Bonaventura et al, 2006a;Kobayashi et al, 2006;Salek-Haddadi et al, 2002;Tyvaert et al, 2008), the 15 patients in the current study constitute a sizable number, but ictal events are still quite infrequently recorded during EEG-fMRI sessions. However, it should be noted that none of the patients had originally been recruited on the basis of their seizure frequency.…”
Section: Ictal Eventsmentioning
confidence: 75%
“…The GLM results from patient #1 were presented previously in Kobayashi et al (2006) and patients #2-4 and #6-9 were presented in Tyvaert et al (2008). A description of the results for all patients is presented in Table 2.…”
Section: Glm Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for human thalamocortical activity during rest has been obtained noninvasively by simultaneous recording of EEG and fMRI. These studies revealed that activity in the alpha range ( 10 Hz) is accompanied by BOLD activity in a thalamocortical network (TCN) with thalamus positively correlated and sensory areas negatively correlated (de Munck et al, 2007;Difrancesco et al, 2008;Feige et al, 2005;Goldman et al, 2002;Lüchinger et al, 2011;Moosmann et al, 2003;Tyvaert et al, 2008). Such functional coupling is typically based on temporal correlation of frequency-specific EEG power fluctuations (convolved with the slow hemodynamic response function) with the co-registered regional BOLD signal in eyes-closed resting state.…”
Section: Introductionmentioning
confidence: 99%